Fluctuations in hours of work and employment across age and gender - Guy Laroque; Sophie Osotimehin (Institute for Fiscal Studies (IFS), 2014)
This paper documents the heterogeneity in labor market volatility across ages and gender in the United States over 1976-2014. We separate fluctuations in hours worked into fluctuations in the average number of hours per worker (the intensive margin) and fluctuations in the number of individuals at work (the extensive margin) and examine the relative importance of these two margins for each demographic group. We then compute the contribution of each demographic group to the change in aggregate hours worked over the business cycle. We discuss the implications of our findings for theories of labor market fluctuations.
Keywords: E24; E32; J21; 330